Применение феррогранатовых эпитаксиальных структур в сверхвысокочастотной электронике - Yushchuk, S. I.; Yuryev, S. A.; Kostyuk, P. S.; Bondar, V. I. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
Single-crystal iron-yttrium garnet (IYG) films with thicknesses ranging from a few micrometers to 92 μm were grown using the liquid-phase epitaxy method. Three methods of etching FeYG films were used to fabricate devices based on magnetostatic waves: ion etching, liquid-chemical etching, and laser-induced etching. The developed waveguide structures and resonators were used to create planar microwave filters and delay lines.